2020
DOI: 10.3390/ijerph17124362
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Fitness with Intelligence and Academic Achievement in Adolescents

Abstract: Physical fitness, intelligence and academic achievement are being studied from a multidisciplinary perspective. In this line, studies to advance our understanding of intelligence and academic achievement could be relevant for designing school-based programs. Our study analyzed the relationship between components of physical fitness including cardiorespiratory fitness, muscular strength and flexibility and general intelligence and academic achievement in adolescents. We recruited 403 adolescents (53.6% boys) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
2
20
0
2
Order By: Relevance
“…To our knowledge, to date, there is no study exploring the combination of socioeconomic factors, physical fitness, and cognitive functioning in adolescents, focusing on the protective social role of physical fitness. Important to note is that the limited evidence on this area has been performed mainly in developed countries [ 41 , 42 ], using socioeconomic variables as covariates [ 43 , 44 ] and focusing on academic achievements as the primary outcome [ 41 , 42 ]. Only one study involving the present adolescent population showed a positive association between SVI and physical activity, and between physical activity and physical fitness (CRF, MF, and SAF) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date, there is no study exploring the combination of socioeconomic factors, physical fitness, and cognitive functioning in adolescents, focusing on the protective social role of physical fitness. Important to note is that the limited evidence on this area has been performed mainly in developed countries [ 41 , 42 ], using socioeconomic variables as covariates [ 43 , 44 ] and focusing on academic achievements as the primary outcome [ 41 , 42 ]. Only one study involving the present adolescent population showed a positive association between SVI and physical activity, and between physical activity and physical fitness (CRF, MF, and SAF) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has begun to establish an association between physical and cognitive variables, demonstrating that physical activity (PA) is not merely coincidentally related to cognitive function ( Donnelly et al, 2016 ; Fernandes et al, 2018 ; Cadenas-Sanchez et al, 2020 ; Gil-Espinosa et al, 2020 ). In addition to the direct role exercise plays in brain plasticity, PA is important for cognitive development, mood state, learning, memory, and concentration ( Aberg et al, 2009 ; Donnelly et al, 2016 ; Fernandes et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of cardiorespiratory fitness was associated with higher motivation towards physical education. Cardiorespiratory fitness has been strongly associated with other psychological outcomes [ 38 , 39 ]. Specifically, Ishinara et al reported specific associations between physical fitness and motivation via exercise habits in children, but not a direct association between physical fitness and motivation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%